Virtual shaft: Synchronized motion control for real time testing of automotive powertrains. (November 2016) - Andert, J.; Klein, S.; Savelsberg, R.; Pischinger, S.; Hameyer, K.
Abstract: The complexity of automobile powertrains continues to rise, leading to increased development time and effort. Synchronous testing with spatially distributed test benches allows improvements by front-loading of the validation phase. Nevertheless, virtualization of the mechanical interaction of shaft connections is required. A virtual shaft algorithm (VSA) is investigated for synchronized motion control in separate test benches. The behavior of a rigid mechanical shaft is analyzed and modeled. The mechanical shaft is substituted by two electrical motors and a superimposed VSA controller. This virtual shaft is established between two test benches for a combustion engine and a mechanical transmission. Control algorithms for synchronized motion control, known from web machines and force feedback, are analyzed. A controller layout with separate torque and speed controllers is implemented and analyzed through transfer function mathematics. The controllers are parametrized analytically for different gears. The effect of communication delay on the VSA is analyzed by simulation. The open clutch situation is handled by deactivation of the torque feedback. Validation on real test benches shows small deviations for torque and speed. Further work will focus on the necessity of system knowledge for controller layout and on the transient behavior during shifting. Abstract : Highlights: A coupling algorithm for synchronization of automotive test benches is proposed. Torque and speed controllers are developed through transfer function analysis. Evaluation is done by simulation and experiment on real test benches.